Learning was designed using demonstration and role play method to Improve Social Intelligence - St.Wardah Hanafie Das; Muhammad Idrus (Universitas Muhammadiyah Enrekang, 2021)
The main problems studied focus on how to implement demonstration and role play methods, learning outcomes of moral aspects and supporting factors and The barrier aims to determine the process of implementing the Demonstration and Role Playing method from beginning to end and to describe the moral aspects of students after its implementation. As a complement to this thesis, the author uses this type of classroom action research, with a qualitative descriptive approach. Research on problem disclosure as there is data analysis using field research, observation, interviews, and documentation using data analysis, namely, data presentation, data reduction, and drawing conclusions (verification). The results of this study indicate that the implementation of Islamic Education learning in the method of demonstration and role playing, is well executed, effective and efficient, fun and exhilarating. Positive impact for students on learning. Students prefer the learning process of the group discussion method. Group discussions provide a lot of different knowledge and knowledge according to the opinions of each group member from various references. Aspects of Moral personality, discipline, responsibility and empathy that exist in students need to be developed in UPT SMA Negeri 2 Sidrap. Each group member has good character so that it is maintained to improve the learning process to be carried out properly, effectively and efficiently. The morals possessed by each student have an assessment both in the relationship of the school environment and individuals. Have a good social, get a value or award so that it is maintained / improved.